2011
DOI: 10.1177/104063871102300109
|View full text |Cite
|
Sign up to set email alerts
|

Canine C-Reactive Protein Measurements in Cerebrospinal Fluid by a Time-Resolved Immunofluorimetric Assay

Abstract: Abstract. In the current study, the quantification of C-reactive protein (CRP) in cerebrospinal fluid (CSF) of dogs using an adapted time-resolved immunofluorimetric assay (TR-IFMA) was investigated, as well as whether the assay could be used to detect the range of CRP concentrations found in different clinical situations. Intra-and interassay coefficients of variation were below 15% in all cases. The TR-IFMA measured the CRP values in a proportional and linear manner (r 5 0.99); also CRP concentrations measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
2
11
0
3
Order By: Relevance
“…For this reason, CRP was also measured in CSF and blood samples of the same patients to assess the relationship between inflammation and coagulation. In our study, CRP was detected in 182/183 CSF samples, which demonstrates the high sensitivity of the TR‐IFMA method compared with that of other techniques previously reported . Our study showed that CRP is present in the CSF of healthy dogs, a fact that has not been previously reported.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…For this reason, CRP was also measured in CSF and blood samples of the same patients to assess the relationship between inflammation and coagulation. In our study, CRP was detected in 182/183 CSF samples, which demonstrates the high sensitivity of the TR‐IFMA method compared with that of other techniques previously reported . Our study showed that CRP is present in the CSF of healthy dogs, a fact that has not been previously reported.…”
Section: Discussionsupporting
confidence: 71%
“…C‐reactive protein was measured in blood and CSF samples, as previously described, using a TR‐IFMA method . k Results were reported in mg/L.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…subarachnoid hemorrhage6 or vasculitis due to sepsis17); intrathecal production of CRP18 and disruption of glymphatic circulation may also contribute to a lesser extent 19. Even when the blood–brain barrier is intact CRP level in the CSF is directly related to serum CRP because this protein flows from blood into the cerebrospinal space,20 but determination of a CRP index along with IgG index has been proposed in cases of canine Steroid Responsive Meningitis‐Arteritis (SRMA)6 and may also be helpful in cases of blood–brain barrier disruption in equine neurological disease.…”
Section: Discussionmentioning
confidence: 99%
“…No studies have evaluated the stability of CRP in frozen equine serum and spinal fluid, but human serum has been stored up to 11 years at −80°C without any significant change 24. Canine CRP studies have also routinely stored serum and CSF frozen (−20°C) prior to assay 6, 7, 20…”
Section: Discussionmentioning
confidence: 99%